2020
DOI: 10.2147/prbm.s240917
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Mediating Role of Positive and Negative Affects in the Relationship Between Self-Esteem and Happiness</p>

Abstract: Background: Affects, both positive and negative, can act as mediators between self-esteem and happiness. The present study is undertaken among 812 university students in order to examine the relationship between these variables. Methods: The sample included 812 university students-361 men (44.46%) and 451 women (55.54%)who participated voluntarily. The Positive and Negative Affect Scale, Subjective Happiness Scale and Self-Esteem Scale were the instruments used in this study. Results: The results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Regarding how happiness behaves by gender, it cannot be said that the results of different investigations have been conclusive. Some studies [36][37][38] have found that women show higher levels of happiness than men, while others [39][40][41][42][43][44] have found no significant differences in terms of happiness depending on gender. In samples of university students, significant differences by gender have been found.…”
Section: Social Skills Happiness and Gendermentioning
confidence: 99%
“…Regarding how happiness behaves by gender, it cannot be said that the results of different investigations have been conclusive. Some studies [36][37][38] have found that women show higher levels of happiness than men, while others [39][40][41][42][43][44] have found no significant differences in terms of happiness depending on gender. In samples of university students, significant differences by gender have been found.…”
Section: Social Skills Happiness and Gendermentioning
confidence: 99%
“…With the cross-sectional data of the aforementioned variables, we first characterize generativity in relation to inquisitiveness, and second, characterize happiness in relation to inquisitiveness and generativity along with other factors. We decided to rely on cross-sectional data following some previous researches in that the effectiveness of cross-sectional data analyses is argued for identifying correlation and causal relation among psychometric and sociodemographic variables, especially when the causal direction is somewhat obvious or intuitively straightforward [75,76,79]. Specifically, we use mean-based and median regressions to address the two open questions posed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesize that inquisitiveness is an important determinant of happiness and generativity, empirically examining the relationships along with noncognitive, cognitive and sociodemographic factors in a single analytical framework. To this end, we conduct questionnaire surveys with 400 Japanese subjects to collect data, following previous studies that analyze the relationship between behaviors and happiness with cross-sectional data [75][76][77][78][79]. There are several studies that apply cross-sectional data analyses, such as mediation analysis and regressions, to examine the relationships among personality traits, behaviors and happiness [75,76,79].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the study variables with respective indicators. The questionnaire survey was adapted from similar questionnaires as used in previous studies with some modifications related to the COVID-19 outbreak [65,79,81,86,87]. The scales were constructed on the basis of a seven-point Likert-scale ranging from 1, representing "extremely disagree" to 7 representing "extremely agree".…”
Section: Survey Instrumentmentioning
confidence: 99%